2016
DOI: 10.1016/j.hpb.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Parenchymal-sparing hepatectomies (PSH) for bilobar colorectal liver metastases are associated with a lower morbidity and similar oncological results: a propensity score matching analysis

Abstract: In conclusion, PSH resection for bilobar multiple CLMs represents a valid alternative to NON-PSH resection in selected patients with a reduced morbidity and comparable oncological results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 45 publications
4
26
0
1
Order By: Relevance
“…In the current study, however, no difference in radicality was found between groups. This finding is supported by the study of Memeo et al , who also compared patients with bilobar disease undergoing PSH to those undergoing non-PSH and found similar rates of radical resection [ 15 ].…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In the current study, however, no difference in radicality was found between groups. This finding is supported by the study of Memeo et al , who also compared patients with bilobar disease undergoing PSH to those undergoing non-PSH and found similar rates of radical resection [ 15 ].…”
Section: Discussionsupporting
confidence: 54%
“…Yet, studies show that advances are being made in the application of parenchyma-sparing liver surgery, even in patients with technically challenging tumor locations, in which intraoperative ultrasound guidance plays an important role [ 12 , 13 ]. Few studies have shown comparable oncological results when applying PSH compared to more extensive surgery (non-PSH) in patients with bilobar disease; whilst PSH might improve perioperative morbidity and mortality [ 14 , 15 ], a true consensus is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Perioperative outcomes in this study are consistent with earlier reported surgical results after open and laparoscopic PSLR for CLM. 7,[9][10][11][12]28,29 Previous studies have indicated that survival rates were higher in patients with resection margins larger than 10 mm compared to those with the resection margins less than 10 mm. 45,46 Other studies have opposed these findings and indicate that predicted margins of less than 10 mm should not be an exclusion criteria for resection in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…The parenchyma-sparing approach allows radical resection with maximum preservation of liver parenchyma, thereby decreasing the risk of postoperative liver failure and facilitating repeated resections in the case of liver recurrence. [6][7][8][9][10][11][12][13] Laparoscopic liver resection (LLR) has progressively developed during the past two decades and the advantages are well-known. [14][15][16][17][18][19][20] Our experience in LLR has been reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that resection of bilateral CRLM can be achieved with reasonable morbidity, mortality, and oncologic results, and that increased use of parenchymal-sparing approaches is associated with decreased mortality without compromising oncological outcomes. The favourable results of PSLR have been recently confirmed in a multicentric retrospective series of patients who had received LR for multiple (> 3) bilobar CRLM, comparing 331 patients who had received PSLR with 360 who had received non-PSLR, defined as the resection of three or more consecutive liver segments, excluding TSH[ 46 ]. PSLR was associated with lower complications (25% vs 34%; P = 0.04) and fewer Dindo-Clavien grade III and IV complications (10% vs 16%; P = 0.03).…”
Section: Conservative or Parenchymal-sparing Liver Surgerymentioning
confidence: 99%